Preparing Exercises According to Generalize the Motor Program and The levels of Skills and Their Effects on Visual Motor Coordination for Football Goalkeepers of Ages 13 - 15 Years. - Kaioun, Yaarub (Journal of Physical Education, 2016)
The importance of the study to develop the performance of goalkeepers by using some of exercises which preparing by researcher.The problem of the study lies in developing goalkeeper's visual motor coordination don’t dependent on scientific basses to prepare exercises, therefore, the researcher prepare some exercises according to generalize the motor program and the levels of Skills to develop visual motor coordination which is important in goalkeeping.The study aims at preparing some exercises according to generalize the motor program and the levels of skills for football goalkeepers of ages 13 - 15 years، and knowing the impact of the use of these exercises on developing the visual motor coordination for football goalkeepers.The researcher has used the experimental method. Two groups with two tests; pre test and post test are used. The researcher also made many procedures like specifying the subject of the study tools and apparatus of the study and specified the suitable tests for visual motor coordination in addition; he executed pilot study a pre-test, some exercises for the experimental group, and a post- test. After all that the research made suitable statistical treating.After treating data in suitable statistical means which obtained by researcher, He shows the results by using certain tables, The researcher also analyzes and discuss the data and gives the reasons which lead to these results in scientific way.Chapter five contains the conclusions that the researcher concluded after treating the data statistically to show the effect of using the exercises on developing visual motor coordination for football goalkeepers.